High Pressure Liquid Chromatography Identification and Quantification of Morpholine Residual Content in Cobicistat After Derivatization (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A derivatization HPLC procedure has been developed to identify and enumerate morpholine (MPE) in cobicistat (CCT) pharmaceutical active substances. MPE react with acetonitrile solution of 1-Naphthyl isothiocyanate to produce stable MPE derivative. The MPE derivative produced was identified and enumerated by HPLC based procedure. The linearity range of MPE was 0.3002675–1.201070 μg/mL with good squared correlation (0.9995), and limits of detection and quantification were 0.1000 μg/mL and 0.3001 μg/mL, respectively. Low (50% of specification quantity), medium (100% of specification quantity), and high (150% of specification quantity) concentrations of MPE were added in CCT samples to evaluate recovery rate. The added recovery rate ranged from 97.9% to 100.4%. The precision value was 0.79% relative standard deviation. The developed procedure also has good selectivity and robustness. This quantitative procedure for MPE can successfully be implemented to analyse the MPE residual quantities in CCT pharmaceutical active substances.